Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, x^2 + 5x +4
= x^2 + 1x + 4x + 4
= (x^2 + 1x) + (4x + 4)
= x ( x + 1 ) + 4 ( x + 1 )
= (x + 1) (x + 4)
b, x^2 - 6x + 5
= x^2 - 1x - 5x + 5
= (x^2 - 1x) - (5x - 5)
= x (x - 1) - 5 (x - 1)
= (x - 1) (x - 5)
c, x^2 + 7x + 12
= x^2 + 3x + 4x + 12
= (x^2 + 3x) + (4x + 12)
= x (x + 3) + 4 (x + 3)
= (x + 3) (x + 4)
d, 2x^2 - 5x + 3
= 2^x2 - 2x - 3x + 3
= 2x (x - 1) - 3 (x - 1)
= (x-1) (2x - 3)
e, 7x - 3x^2 - 4
= 3x + 4x - 3x^2 - 4
= (3x - 3x^2) + (4x - 4)
= 3x (1 - x) + 4 (x - 1)
= 3x (1-x) - 4 (1 - x)
= (1 - x) (3x - 4)
f, x^2 - 10x + 16
= x^2 - 2x - 8x + 16
= (x^2 - 2x) - (8x - 16)
= x (x - 2) - 8 (x - 2)
= (x - 2) (x - 8)
a, (x+1)(x+4)
b,(x-5)(x-1)
c,(x+3)(x+4)
d,(2x-3)(x-1)
e,(-3x+4)(x-1)
f, (x-8)(x-2)
a) x2 + 7x + 12 = x2 + 3x + 4x + 12 = x( x + 3 ) + 4( x + 3 ) = ( x + 3 )( x + 4 )
b) x2 - 10x + 16 = x2 - 2x - 8x + 16 = x( x - 2 ) - 8( x - 2 ) = ( x - 2 )( x - 8 )
c) x2 + 6x + 8 = x2 + 2x + 4x + 8 = x( x + 2 ) + 4( x + 2 ) = ( x + 2 )( x + 4 )
d) x2 - 8x + 15 = x2 - 3x - 5x + 15 = x( x - 3 ) - 5( x - 3 ) = ( x - 3 )( x - 5 )
e) x2 - 8x - 9 = x2 + x - 9x - 9 = x( x + 1 ) - 9( x + 1 ) = ( x + 1 )( x - 9 )
f) x2 + 14x + 48 = x2 + 6x + 8x + 48 = x( x + 6 ) + 8( x + 6 ) = ( x + 6 )( x + 8 )
a,\(\left(x-5\right)^2-16=\left(x-5\right)^2-4^2=\left(x-5-4\right)\left(x-5+4\right)=\left(x-9\right)\left(x-1\right)\)
\(x^3+9x^2+26x+24\)
\(=x^3+3x^2+6x^2+18x+8x+24\)
\(=\left(x^3+3x^2\right)+\left(6x^2+18x\right)+\left(8x+24\right)\)
\(=x^2\left(x+3\right)+6x\left(x+3\right)+8\left(x+3\right)\)
\(=\left(x+3\right)\left(x^2+6x+8\right)\)
\(=\left(x+3\right)\left(x^2+2x+4x+8\right)\)
\(=\left(x+3\right)\left[\left(x^2+2x\right)+\left(4x+8\right)\right]\)
\(=\left(x+3\right)\left[x\left(x+2\right)+4\left(x+2\right)\right]\)
\(=\left(x+3\right)\left(x+2\right)\left(x+4\right)\)
\(15^3+29x^2-8x-12=15x^3+30x^2-x^2-2x-6x-12\)
= \(15x^2.\left(x+2\right)-x.\left(x+2\right)-6.\left(x+2\right)\)= \(\left(x+2\right).\left(15x^2-x-6\right)\)
= \(\left(x+2\right).\left(15x^2-10x+9x-6\right)\)= \(\left(x+2\right).\left(3x-2\right).\left(5x+3\right)\)
\(x^3+9x^2+26x+24=x^3+3x^2+6x^2+18x+8x+24\)\(=x.^2\left(x+3\right)+6x.\left(x+3\right)+8.\left(x+3\right)\)\(=\left(x+3\right).\left(x^2+6x+8\right)\)\(\left(x+3\right).\left(x^2+2x+4x+8\right)=\left(x+2\right).\left(x+3\right).\left(x+4\right)\)
Ta có : 15x3 + 29x2 - 8x - 12
= 15x3 + 30x2 - x2 - 8x - 12
= 15x(x + 2) - (8x + 16) - (x2 - 4)
= 15x(x + 2) - 8(x + 2) - (x - 2)(x + 2)
= (x + 2)(15x - 8 - x + 2)
= (x + 2) (14x - 6)
click zô nha >_<
a) = (3x)^2 + 2.3x.5+ 5^2 = (3x+5)^2
b) = (2/3x)^2-(4y)^2=(2/3x-4y)(2/3x+4y)
c) = -(9x^4-12/5x^2y^2+4/25y^4) = -[(3x^2)^2 - 2.3x^2.2/5y^2 + (2/5y^2)^2]= -(3x^2-2/5y^2)^2
d) = (x-5)^2 - 4^2= (x-5+4)(x-5-4) = (x-1)(x-9)
e) = (2x)^3 + 3.(2x)^2.(5y) + 3.(2x).(5y)^2 + (5y)^3 = (2x+5y)^3
f) = (8x)^2 - (8a+b)^2 = (8x-8a-b)(8x+8a+b)
g) = (7x-4-2x-1)(7x-4+2x+1) = (5x-5)(9x-3) = 5(x-1).3(x-3)=15(x-1)(x-3)
h) = (x-y)(x+y)- 2(x+y) = (x+y)(x-y-2)
# Chúc bạn học tốt #
a) x2 + 7x + 12
= x2 + 3x + 4x + 12
= ( x2 + 3x ) + ( 4x + 12 )
= x( x + 3 ) + 4( x + 3 )
= ( x + 3 )( x + 4 )
b) x4 + 8x2 + 16
= ( x2 )2 + 2.x2.4 + 42
= ( x2 + 4 )2
c) x2 + 26x + 25
= x2 + x + 25x + 25
= ( x2 + x ) + ( 25x + 25 )
= x( x + 1 ) + 25( x + 1 )
= ( x + 1 )( x + 25 )
a) \(x^2+7x+12\)
\(x^2+4x+3x+12\)
\(x\left(x+4\right)+3\left(x+4\right)\)
\(\left(x+4\right)\left(x+3\right)\)
b) \(x^4+8x^2+16\)
\(\left(x^2+4\right)^2\)
c) \(x^2+26x+25\)
\(x^2+x+25x+25\)
\(x\left(x+1\right)+25\left(x+1\right)\)
\(\left(x+25\right)\left(x+1\right)\)